HUBUNGAN ANTARA PENGETAHUAN DENGAN TINGKAT KECEMASAN IBU SAAT MENGHADAPI HOSPITALISASI PADA ANAK DI RUANG ANAK RSUD PAREâKEDIRI TAHUN 2008 - Lenawati, Helena; Puspitasari, Hendrit (Jurnal AKP, 2010)
Hospitalization of child is a process because of a reason to obligate a child to stay in the hospital thathave planning or emergency, endure treatment and therapy until repatriating to home. A Child is the part oftheir parent life so, if there are any experience bothering them, their parent will be worry.The objective of this research is to investigate the knowledge relation with plead of mother level in face ofhospitalization a child. This research is use analytic cross sectional design. The sample is taken away frommothers that waiting their child. In pediatric unit with size sample 28 persons, it is using purposive samplingtechnique.Result this research show from 11 responder having knowledge of good, 7 responder having lightanxiety level (63,6%), 3 responder having medium anxiety level (27,3%) and responder having heavy anxietylevel (9,1%).Progressivey goodness knowledge of mother, it is decrease the anciety level in face of hospitalization achild. To lessen the anxiety level of parent, healthy officer is suggested to give more information abouthospitalization and also medical proceeds are about treatment of a child.